Fever or Forgotten Wings: The Relevance of Heidegger's Call of Conscience to Psychotherapy (Existential Analysis: Journal of the Society for Existential Analysis, 2001)
The intention of this paper is to pursue the theme in The Phenomenology of the Call of Conscience (Rennie: 2000) and to explore what relevance Heidegger's notion may have to psychotherapy. We will begin by considering the ambiguous relationship therapists often have with Heidegger's text and attempt to elucidate some of the problems inherent in translating his ideas into psychotherapy. Against this background, we will consider how the phenomenology of the call of conscience is therapeutically germane by looking at aspects such as dialogue, transparency, existential guilt and Heidegger's description of listening and attending. It will also be posited that the poetics of Heidegger's language is closely allied to the call of conscience, suggesting that his literary style is not so much an obscuration, but a way in for readers.